Designing an Adaptive Curriculum Framework for Nonformal Education in the Era of Artificial Intelligence: A Digital Andragogy Approach - Rosyanafi, Rofik; Lestari, Gunarti; Nugroho, Rivo; Krishnandya, Kharizha; Wasil, Mohammad; Nuraini, Febritesna; Villaflor, Edwin Jaimes (The Indonesian Institute of Science and Technology Research, 2026)
The rapid advancement of artificial intelligence (AI) has redefined the dynamics of adult and community learning, calling for curriculum models that combine technological adaptability with human-centered pedagogy. This study designs and validates an Adaptive Curriculum Framework for Nonformal Education (ACF-NE) grounded in digital andragogy principles, AI-based adaptivity, and community contextualization. Employing a Design and Development Research (DDR) approach, data were collected through document analysis, focus group discussions, and expert validation across five community learning centers and two vocational institutions in East Java, Indonesia. The iterative design process produced three core dimensions—(1) learner autonomy and experiential relevance, (2) AI-driven personalization and feedback, and (3) socio-cultural integration of community learning. Quantitative validation involving four experts yielded high consensus scores across relevance (M = 4.68), clarity (M = 4.41), feasibility (M = 4.37), and innovation (M = 4.42). Thematically, results indicate that AI can enhance adult autonomy when positioned as a facilitative partner rather than an instructional replacement. The final ACF-NE model integrates adaptive scaffolding with human mediation, establishing a co-learning ecology that aligns digital personalization with cultural responsiveness. This study contributes theoretically by extending andragogy into the AI era through the construct of contextual adaptivity, and practically by offering a replicable framework for human-centered digital transformation in nonformal education.